Constitutionally High Serotonin Tone Favors Obesity: Study on Rat Sublines With Altered Serotonin Homeostasis - Kesić, Maja; Baković, Petra; Horvatiček, Marina; Proust, Bastien Lucien Jean; Štefulj, Jasminka; Čičin-Šain, Lipa (Frontiers in Neuroscience, 2020)
Central and peripheral pools of biogenic monoamine serotonin (5-hydroxytryptamine, 5HT) exert opposite effects on the body weight regulation: increasing of brain 5HT activity is expected to decrease body weight, while increasing peripheral 5HT activity will increase body weight and adiposity. In a genetic model of rats with constitutionally high or low 5HT homeostasis (hyper/hyposerotonergic rats), we have studied how individual differences in endogenous 5HT tone modulates net energy balance of the organism. The high-5HT and low-5HT sublines of the model were developed by selective breeding toward extreme platelet activities of 5HT transporter, a key molecule determining 5HT bioavailability/activity. In animals from high-5HT and low-5HT sublines, we assessed physiological characteristics associated with body weight homeostasis and expression profile of a large scale of body weight-regulating genes in hypothalamus, a major brain region controling energy balance. Results showed that under standard chow diet, animals from the high-5HT subline, as compared to low-5HT animals, have life-long increased body weight (by 12%), higher absolute daily food intake (by 9%) and different pattern of fat distribution (larger amount of white adipose tissue and lower amount of brown adipose tissue). A large number of body weight-regulating hypothalamic genes were analyzed for their mRNA expression: 24 genes by RT-qPCR (N=9-10 rats/subline) including neuropeptides and their receptors, growth factors, transcriptional factors and receptors for peripheral signals, and total of 84 genes of various classes by PCR array (pools of 6 rats/subline). Only few genes showed significant differences in mRNA expression levels between 5HT sublines (e.g. neuropeptideY receptor, fibroblast growth factor 10) but high-5HT animals displayed a clear trend to upregulation of mRNAs for a number of orexigenic signaling peptides, their receptors, and other molecules with orexigenic activity. Receptors for peripheral signals (leptin, insulin) and molecules in their downstream signaling were not altered indicating no changes in central insulin/leptin resistance. At the protein level there were no differences in the content of hypothalamic leptin receptor between 5HT sublines but significant sex and age effects were observed. Results show that higher constitutive/individual 5HT tone favors higher body weight and adiposity probably due to concurrent upregulation of several hypothalamic orexigenic pathways.